Compound and battery containing same

A phosphorus-sulfur compound with a disulfide bond is used as a binder in all-solid batteries to maintain ionic conductivity and improve binding properties, addressing the limitations of conventional binders and enhancing battery performance.

JP7620292B2Active Publication Date: 2025-01-23IDEMITSU KOSAN CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2021533115
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-07-18
Filing Date
2020-07-17
Publication Date
2025-01-23
Estimated Expiration
2040-07-17

AI Technical Summary

Technical Problem

Conventional binders used in all-solid batteries, such as polyvinylidene fluoride and carboxymethyl cellulose, increase ionic conductivity but decrease ionic conductivity when added in large amounts to enhance binding properties, leading to capacity deterioration and reduced battery performance.

Method used

A compound containing phosphorus and sulfur with a disulfide bond is used as a binder, which maintains ion conductivity while providing strong binding properties, thereby suppressing the decrease in ionic conductivity and enhancing battery performance.

Benefits of technology

The compound with a disulfide bond effectively binds battery layers, maintaining ionic conductivity and improving cycle characteristics, while also offering superior heat resistance and flexibility, thus enhancing the overall battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007620292000003
    Figure 0007620292000003
  • Figure 0007620292000004
    Figure 0007620292000004
  • Figure 0007620292000005
    Figure 0007620292000005
Patent Text Reader

Abstract

A compound including phosphorus and sulfur as constituent elements and having a peak derived from a disulfide bond that bonds two phosphorus elements in Raman spectroscopy.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a compound and a battery containing the same. [Background technology]

[0002] An all-solid-state battery such as an all-solid-state lithium ion battery usually includes a positive electrode layer, a solid electrolyte layer (sometimes simply referred to as an "electrolyte layer"), and a negative electrode layer. By incorporating a binder into these layers, each layer or a laminate of these layers can be formed into a sheet.

[0003] Non-Patent Documents 1 and 2 disclose the polymerization of PS4 on the surface of an electrode active material. Non-Patent Document 3 discloses the change in chemical structure of 70Li2S-30P2S5 due to heat treatment. [Prior art documents] [Non-patent literature]

[0004] [Non-Patent Document 1] Masato Sumita and 2 others, "Possible Polymerization of PS4 at a Li3PS4 / FePO4 Interface with Reduction of the FePO4 Phase", The Journal of Physical Chemistry C, April 24, 2017, Vol. 121, p. 9698-9704 [Non-Patent Document 2] Takashi Hakari and 9 others, "Structural and Electronic-State Changes of a Sulfide Solid Electrolyte during the Li Deinsertion-Insertion Processes", Chemistry of Materials, May 3, 2017, Vol. 29, p. 4768-4774 [Non-Patent Document 3] Yuichi Hasegawa, 'Chemical structure analysis of sulfide-based solid electrolyte 70Li2S-30P2S5', [online], February 1, 2018, Toray Research Center, Inc., [Retrieved July 9, 2019], Internet〈URL:https: / / www.toray-research.co.jp / technical-info / trcnews / pdf / 201802-01.pdf〉 Summary of the Invention

[0005] It is possible to use polyvinylidene fluoride (PVDF) or carboxymethyl cellulose (CMC) as a binder. However, when the amount of such a binder is increased in order to obtain binding between the materials (e.g., electrode mixture) that constitute the layer, the ion conductivity decreases. Therefore, a compound that has ion conductivity and can function as a binder is desired.

[0006] An object of the present invention is to provide a compound that can be used as a binder for a battery and that can suppress a decrease in ion conductivity, and a battery containing the compound.

[0007] As a result of extensive investigations, the present inventors have found that a compound containing phosphorus and sulfur as constituent elements and having a disulfide bond can be used as a binder having ion conductivity, and have completed the present invention. According to one embodiment of the present invention, there is provided a compound (hereinafter, sometimes referred to as "compound α") that contains phosphorus and sulfur as constituent elements and has a peak derived from a disulfide bond that bonds the two phosphorus elements in Raman spectroscopy.

[0008] According to the present invention, it is possible to provide a compound having ion conductivity that can be used as a binder for a battery, and a battery including the compound. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 shows the results of powder X-ray analysis of compound α. [Diagram 2] 1 is a solid-state 31P-NMR chart of compound α obtained in Example 3. [Diagram 3] 1 is a Raman spectrum of compound α. [Figure 4] 1 shows Raman spectra of compound α (before and after toluene treatment). [Diagram 5] FIG. 1 is a diagram showing the results of measuring the ionic conductivity of compound α. [Figure 6] 1 is a scanning electron microscope image of compound α before press molding. [Figure 7] 1 is a scanning electron microscope image of compound α after press molding. [Figure 8] 1 is a photograph of the coating solution prepared in Example 4. [Figure 9] 1 is a photograph of the coating solution prepared in Example 5. [Figure 10] 1 is a photograph of the coating solution prepared in Comparative Example 2. [Figure 11] FIG. 13 shows the results of initial charge / discharge of the cell of Example 9. [Figure 12] FIG. 13 is a graph showing the results of cycle characteristics of the cell of Example 9. [Figure 13] 1 is a Cole-Cole plot of the cell of Example 9. [Figure 14] FIG. 13 shows the results of initial charge / discharge of the cell of Example 11. [Figure 15] FIG. 13 is a graph showing the results of cycle characteristics of the cell of Example 11. [Figure 16] 1 is a solid-state 31P-NMR chart of compound α obtained in Example 13. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The following describes the embodiments of the present invention. It should be noted that a combination of two or more of the individual preferred embodiments of the present invention described below is also a preferred embodiment of the present invention.

[0011] <Compound α> Compound α according to one embodiment of the present invention contains phosphorus and sulfur as constituent elements, and has a peak derived from a disulfide bond that bonds the two phosphorus elements in Raman spectroscopy.

[0012] Compound α according to one embodiment of the present invention has a Raman shift of 425 cm -1 More than 500cm -1 Less than 440cm, preferably 440cm -1 More than 490cm -1 Less than or equal to 460cm, more preferably -1 More than 480cm -1 It has a peak in the following range (hereinafter also referred to as "Peak A") and a Raman shift of 370 cm -1 Over 425cm -1 Less than 380cm, preferably -1 Over 423cm -1 Less than or equal to 390cm, more preferably -1 More than 420cm -1 It can be identified by having a peak (hereinafter also referred to as "peak B") in the following range. Incidentally, compound α according to one embodiment of the present invention may be identified as having a disulfide bond (SS) by the presence of peak A. Peak A is derived from the disulfide bond (SS) that connects the two phosphorus atoms in compound α. Peak B is derived from PS4 3- This is due to the symmetric stretching caused by the PS bonds in the unit (also called the PS4 structure).

[0013] The Raman spectroscopic analysis of compound α is carried out by the method described in the Examples. At this time, it is important to perform the measurement after treating compound α with toluene. This is to remove elemental sulfur that may be mixed in compound α. Elemental sulfur has a peak at a position that may overlap with peak A. Therefore, by removing elemental sulfur, peak A derived from compound α can be well measured. The toluene treatment is carried out by the procedure described in the Examples.

[0014] Compound α according to one embodiment of the present invention preferably contains one or more elements selected from the group consisting of lithium, sodium, and magnesium as constituent elements. In one embodiment, these constituent elements are bonded to S in compound α by ionic bonds.

[0015] <Battery binder> A battery binder according to one embodiment of the present invention (hereinafter, referred to as battery binder (A)) contains the above-mentioned compound α. The battery binder (A) may further contain a halogen. The halogen may be derived from an oxidizing agent or the like used in producing compound α. The halogen may be one or more selected from the group consisting of iodine, fluorine, chlorine and bromine. The halogen may be iodine or bromine.

[0016] The form of the halogen is not particularly limited, and may be, for example, one or more selected from the group consisting of a salt of one or more elements selected from the group consisting of lithium, sodium, magnesium, and aluminum and a halogen, and a halogen alone. Examples of the salt include LiI, NaI, MgI2, AlI3, LiBr, NaBr, MgBr2, and AlBr3. Among these, LiI and LiBr are preferred from the viewpoint of ion conductivity. Examples of the halogen alone include iodine (I2), fluorine (F2), chlorine (Cl2), and bromine (Br2). Among these, iodine (I2) and bromine (Br2) are preferred from the viewpoint of reducing corrosion when the halogen remains in the binder (A). In one embodiment, the battery binder (A) may have higher ion conductivity by including a halogen as the above-mentioned salt.

[0017] The content of the compound α in the battery binder (A) is not particularly limited, and for example, from the viewpoint of the binding strength of the active material and the solid electrolyte described later, when the total mass of the battery binder (A) is taken as 100 mass%, the content is 50 mass% or more, 60 mass% or more, 70 mass% or more, 80 mass% or more, 85 mass% or more, 90 mass% or more, 95 mass% or more, 98 mass% or more, 99 mass% or more, 99.5 mass% or more, 99.8 mass% or more, or 99.9 mass% or more.

[0018] The content of the halogen-containing substance (elemental halogen and halogen compound) in the battery binder (A) is not particularly limited, and from the viewpoint of the conductivity of the carrier ions and the binding strength of the active material and the solid electrolyte, for example, when the total mass of the battery binder (A) is taken as 100 mass%, it may be 50 mass% or less, 40 mass% or less, 30 mass% or less, 20 mass% or less, 15 mass% or less, 10 mass% or less, 8 mass% or less, 5 mass% or less, 3 mass% or less, 2 mass% or less, 1 mass% or less, 0.5 mass% or less, 0.1 mass% or less, 0.05 mass% or less, or 0.01 mass% or less. The battery binder (A) may be substantially 100% by mass of the compound α, or the compound α and a halogen-containing substance.

[0019] The battery binder (A) can be used in various batteries. Examples of the battery include secondary batteries such as lithium ion batteries. The battery can be an all-solid-state battery. The "binder" is blended with any of the elements of such a battery, for example, one or more selected from the group consisting of a battery electrode mixture layer and an electrolyte layer, and can exert a binding property (binding force) for binding other components contained in the element (for example, layer) to maintain the unity.

[0020] Conventional battery electrode mixture layers (e.g., positive or negative electrodes described later) have difficulty in following the expansion and contraction (volume change) of the electrode active material accompanying charge and discharge, etc., and are prone to problems such as capacity degradation. The electrolyte layer adjacent to the battery electrode mixture layer may also be affected by the volume change of the battery electrode mixture layer, and may cause problems such as degradation. In contrast, by using the battery binder (A), the battery electrode mixture layer or electrolyte layer can absorb the volume change due to the flexibility of the battery binder (A), and capacity degradation can be prevented. This allows the battery to exhibit excellent cycle characteristics. In addition, since the battery binder (A) itself can have ion conductivity, even if the amount of the battery binder (A) added is increased to increase the binding between the materials (e.g., electrode mixtures) constituting the layer, the decrease in ion conductivity can be suppressed, and the battery characteristics can be exhibited well. Furthermore, in one embodiment, the battery binder (A) has superior heat resistance compared to ordinary organic binders and polymer solid electrolytes (eg, polyethylene oxide, etc.), and therefore the operating temperature range of the battery can be expanded.

[0021] <Electrode mixture layer or electrolyte layer for batteries> The battery electrode mixture layer or electrolyte layer according to one embodiment of the present invention contains the battery binder (A) described above. In one embodiment, the battery binder (A) is unevenly distributed or uniformly distributed (dispersed) in the battery electrode mixture layer or electrolyte layer. In one embodiment, the battery binder (A) is uniformly distributed (dispersed) in the layer, which better maintains the integrity of the layer.

[0022] The battery electrode mixture layer or electrolyte layer preferably contains a solid electrolyte (hereinafter referred to as solid electrolyte (B)) other than the battery binder (A). The solid electrolyte (B) is not particularly limited, and for example, an oxide solid electrolyte or a sulfide solid electrolyte can be used. Among them, a sulfide solid electrolyte is preferable, and specifically, an argyrodite type crystal structure, a Li3PS4 crystal structure, a Li4P2S6 crystal structure, a Li7P3S 11 Crystal structure, Li 4-x Ge 1-x P xS4 thio-LISICON Region II crystal structure, Li 4-x Ge 1-x P x Examples of such solid electrolytes include sulfide solid electrolytes having a crystal structure similar to the S4 thio-LISICON Region II type (hereinafter sometimes abbreviated as RII type crystal structure).

[0023] Examples of the electrode mixture layer for a battery include a positive electrode and a negative electrode. When the electrode mixture layer for a battery is a positive electrode, the positive electrode may further include a positive electrode active material. The positive electrode active material is a material capable of inserting and extracting lithium ions, and any material known in the field of batteries as a positive electrode active material may be used.

[0024] Examples of the positive electrode active material include metal oxides, sulfides, etc. Sulfides include metal sulfides and nonmetal sulfides. The metal oxide is, for example, a transition metal oxide. Specifically, V2O5, V6O 13 , LiCoO2, LiNiO2, LiMnO2, LiMn2O4, Li(Ni a Co b Mn c )O2(where 0 <a<1、0<b<1、0<c<1、a+b+c=1)、LiNi 1-Y Co Y O2, LiCo 1-Y Mn Y O2, LiNi 1-Y Mn Y O2 (where 0≦Y<1), Li(Ni a Co b Mn c )O4(0 <a<2、0<b<2、0<c<2、a+b+c=2)、LiMn 2-Z Ni Z O4, LiMn 2-Z Co Z O4 (where 0 <Z<2)、LiCoPO4、LiFePO4、CuO、Li(Ni a Co b Al c)O2 (where 0 < a < 1, 0 < b < 1, 0 < c < 1, and a + b + c = 1) and the like can be mentioned. Examples of the metal sulfide include titanium sulfide (TiS2), molybdenum sulfide (MoS2), iron sulfide (FeS, FeS2), copper sulfide (CuS), nickel sulfide (Ni3S2), and the like. In addition, examples of the metal oxide include bismuth oxide (Bi2O3), bismuth lead oxide (Bi2Pb2O5), and the like. Examples of the non-metal sulfide include organic disulfide compounds, carbon sulfide compounds, and the like. In addition to the above, niobium selenide (NbSe3), metallic indium, and sulfur can also be used as the positive electrode active material.

[0025] When the electrode composite layer for the battery is the negative electrode, the negative electrode can further contain a negative electrode active material. The negative electrode active material can be a carbon material such as graphite, natural graphite, artificial graphite, hard carbon, soft carbon; a composite metal oxide such as a polyacene-based conductive polymer, lithium titanate; a compound that forms an alloy with lithium such as silicon, silicon alloy, silicon composite oxide, tin, tin alloy, etc., materials commonly used in lithium-ion secondary batteries. Among these, the negative electrode active material preferably contains one or more selected from the group consisting of Si (silicon, silicon alloy, silicon-graphite composite, silicon composite oxide, etc.) and Sn (tin, tin alloy).

[0026] One or both of the positive electrode and the negative electrode can contain a conductive assistant. When the electron conductivity of the active material is low, it is preferable to add a conductive assistant. Thereby, the rate characteristics of the battery can be improved.

[0027] Specific examples of the conductive assistant are preferably substances containing at least one element selected from the group consisting of carbon materials, nickel, copper, aluminum, indium, silver, cobalt, magnesium, lithium, chromium, gold, ruthenium, platinum, beryllium, iridium, molybdenum, niobium, osmium, rhodium, tungsten, and zinc, and more preferably simple carbon having high conductivity, carbon materials other than simple carbon, or simple metals, mixtures, or compounds containing nickel, copper, silver, cobalt, magnesium, lithium, ruthenium, gold, platinum, niobium, osmium, or rhodium. Specific examples of carbon materials include carbon black such as Ketjen Black, Acetylene Black, Denka Black, Thermal Black, and Channel Black; graphite, carbon fiber, activated carbon, etc., which can be used alone or in combination of two or more. Among them, acetylene black, including Denka Black, and Ketjen Black, which have high electronic conductivity, are preferred.

[0028] The electrolyte layer contains a battery binder (A) and may contain a solid electrolyte (B) other than the battery binder (A) as an optional component.

[0029] The composition of the positive electrode is not particularly limited, and may be, for example, positive electrode active material: solid electrolyte (B): battery binder (A): conductive assistant=50-99:0-30:1-30:0-30 in mass ratio. The positive electrode may comprise 30% by mass or more, 50% by mass or more, 80% by mass or more, 90% by mass or more, 95% by mass or more, 98% by mass or more, or 99% by mass or more of the positive electrode active material, the solid electrolyte (B), the battery binder (A), and the conductive assistant.

[0030] The composition of the negative electrode is not particularly limited, and may be, for example, a mass ratio of negative electrode active material: solid electrolyte (B): battery binder (A): conductive assistant=40-99:0-30:1-30:0-30. The negative electrode may comprise 30% by mass or more, 50% by mass or more, 80% by mass or more, 90% by mass or more, 95% by mass or more, 98% by mass or more, or 99% by mass or more of the negative electrode active material, the solid electrolyte (B), the battery binder (A), and the conductive assistant.

[0031] The composition of the electrolyte layer is not particularly limited, and may be, for example, a mass ratio of solid electrolyte (B):battery binder (A)=99.9:0.1 to 0:100. When the mass ratio of the solid electrolyte (B) is 0, the battery binder (A) can also function as a solid electrolyte. The electrolyte layer may comprise 30% by mass or more, 50% by mass or more, 80% by mass or more, 90% by mass or more, 95% by mass or more, 98% by mass or more, 99% by mass or more, or 99.9% by mass or more of the solid electrolyte (B) and the battery binder (A).

[0032] The method of forming a layer containing compound α, for example, the method of forming each layer constituting the above-mentioned battery, is not particularly limited, and examples thereof include coating methods. In the coating method, a coating liquid in which the components contained in each layer are dissolved or dispersed in a solvent can be used. As the solvent contained in the coating liquid, chain, cyclic or aromatic ethers (e.g., dimethyl ether, dibutyl ether, tetrahydrofuran, anisole, etc.), esters (e.g., ethyl acetate, ethyl propionate, etc.), alcohols (e.g., methanol, ethanol, etc.), amines (e.g., tributylamine, etc.), amides (e.g., N-methylformamide, etc.), lactams (e.g., N-methyl-2-pyrrolidone, etc.), hydrazine, acetonitrile, etc. can be used. A layer (dried coating film) is formed by drying the solvent after coating. From the viewpoint of ease of drying the solvent, anisole is preferred. The drying method is not particularly limited, and for example, one or more means selected from the group consisting of heat drying, air drying, and reduced pressure drying (including vacuum drying) can be used.

[0033] The member to which the coating liquid is applied is not particularly limited. The formed layer may be used in a battery together with the member, or the formed layer may be peeled off from the member and used in a battery. In one embodiment, the coating liquid for forming a positive electrode is applied onto a positive electrode current collector. In one embodiment, the coating liquid for forming a negative electrode is applied onto a negative electrode current collector. In one embodiment, the coating liquid for forming an electrolyte layer is applied onto a positive electrode or a negative electrode. In one embodiment, the coating liquid for forming an electrolyte layer is applied onto an easily peelable member, and then the formed layer is peeled off from the easily peelable member and placed between the positive electrode and the negative electrode.

[0034] It is preferable to press the dried coating film (layer). The pressing may be any pressing method that compresses the layer. For example, pressing can be performed so as to reduce the porosity in the layer. The pressing device is not particularly limited, and for example, a roll press or a uniaxial press can be used. The temperature during pressing is not particularly limited, and may be about room temperature (23°C), or may be lower or higher than room temperature. By pressing, the battery binder (A) contained in the layer is suitably deformed due to its flexibility, and the formation of an interface between the electrode mixtures contained in the layer is promoted. This further improves the battery characteristics.

[0035] The pressing may be performed on each layer, or on a laminate of multiple layers (for example, a "battery sheet" described below) so as to press the multiple layers in the lamination direction.

[0036] <Battery sheet> The battery sheet according to one embodiment of the present invention includes at least one selected from the group consisting of the electrode mixture layer and the electrolyte layer described above. The battery sheet exhibits excellent flexibility by including the compound α or the battery binder (A), and is prevented from breaking or peeling off from the current collector.

[0037] <Battery> A battery according to one embodiment of the present invention contains the above-mentioned compound α. In one embodiment, the battery is an all-solid-state battery. In one embodiment, the all-solid-state battery includes a laminate including, in this order, a positive electrode current collector, a positive electrode, an electrolyte layer, a negative electrode, and a negative electrode current collector. As the current collector, a plate or foil made of copper, magnesium, stainless steel, titanium, iron, cobalt, nickel, zinc, aluminum, germanium, indium, lithium, or an alloy thereof can be used. In the battery, it is preferable that at least one selected from the group consisting of the positive electrode, the electrolyte layer, and the negative electrode contains the compound α.

[0038] In the above description (and in the examples described later), the use of compound α in a battery has been mainly described, but the present invention is not limited thereto. Compound α has excellent flexibility, ionic conductivity, and the like, and therefore can be widely used in various applications.

[0039] <Method of producing compound α> A method for producing compound α according to one embodiment of the present invention includes adding an oxidizing agent to a raw material compound containing phosphorus and sulfur as constituent elements, and reacting the raw material compound with the oxidizing agent. By reacting the raw material compound with an oxidizing agent, the above-mentioned compound α is obtained as a product.

[0040] The raw material compound (hereinafter referred to as raw material compound (C)) which is the raw material of this embodiment contains phosphorus and sulfur as constituent elements. The raw material compound (C) preferably contains, as a constituent element, one or more elements selected from the group consisting of lithium, sodium, magnesium and aluminum. In one embodiment, the raw material compound (C) preferably contains a PS4 structure. Examples of raw material compounds containing a PS4 structure include Li3PS4, Li4P2S 7、 Examples of the PS4 structure include Na3PS4 and Na4P2S7. The starting compound (C) may contain two or more PS4 structures, such as Li4P2S7 and Na4P2S7. When the starting compound (C) contains two adjacent PS4 structures, the two PS4 structures may share one S atom. Li3PS4 can be produced, for example, by reacting Li2S and P2S5 in the presence of a dispersion medium by a mechanochemical method (mechanical milling). Examples of the dispersion medium include n-heptane. For the mechanochemical method, for example, a planetary ball mill can be used. In one embodiment, the compound α can be produced by reacting Li2S, P2S5, and an oxidizing agent in the presence of a dispersion medium (e.g., n-heptane, etc.) by a mechanochemical method (mechanical milling). Again, for example, a planetary ball mill or the like can be used for the mechanochemical method. In the above description, Na2S may be used in place of Li2S.

[0041] Examples of the oxidizing agent include a halogen alone, oxygen, ozone, oxides (Fe2O3, MnO2, Cu2O, Ag2O, etc.), oxoacid salts (chlorates, hypochlorites, iodates, bromates, chromates, permanganates, vanadates, bismuthates, etc.), peroxides (lithium peroxide, sodium peroxide, etc.), halide salts (AgI, CuI, PbI2, AgBr, CuCl, etc.), cyanide salts (AgCN, etc.), thiocyanates (AgSCN, etc.), and sulfoxides (dimethyl sulfoxide, etc.). In one embodiment, the oxidizing agent is preferably a halogen alone from the viewpoint of increasing ion conductivity by a metal halide generated as a by-product. The "metal halide" may be a salt of one or more elements selected from the group consisting of lithium, sodium, magnesium, and aluminum derived from the raw material compound (C) and a halogen (for example, a lithium halide when the raw material compound (C) contains lithium). Examples of the halogen element include iodine (I2), fluorine (F2), chlorine (Cl2), and bromine (Br2). From the viewpoint of obtaining higher ionic conductivity, the halogen element is preferably iodine (I2) or bromine (Br2). The oxidizing agent may be used alone or in combination of two or more kinds.

[0042] In one embodiment, when the raw material compound (C) is Li3PS4 and the oxidizing agent is I2, it is presumed that the reactions shown in the following reaction formulas (1) to (3) proceed. In one embodiment, compound α has a PSS chain (a chain consisting of repeating repeating units made of PSS) (reaction formulas (1) and (2)). In one embodiment, the PSS chain of compound α forms a branch (reaction formula (3)). In one embodiment, two phosphorus elements and a disulfide bond connecting these two phosphorus elements constitute the PSS chain. [ka]

[0043] The molar ratio of Li3PS4 to I2 (Li3PS4:I2) used in the reaction (mixed) is not particularly limited and may be, for example, 10:1 to 1:10, 5:1 to 1:5, 3:1 to 1:3, 2:1 to 1:2, 4:3 to 3:4, 5:4 to 4:5, or 8:7 to 7:8. The amount of I2 may be 0.1 molar parts or more, 0.2 molar parts or more, 0.5 molar parts or more, 0.7 molar parts or more, or 1 molar part or more, and may be 300 molar parts or less, 250 molar parts or less, 200 molar parts or less, 180 molar parts or less, 150 molar parts or less, 130 molar parts or less, 100 molar parts or less, 80 molar parts or less, 50 molar parts or less, 30 molar parts or less, 20 molar parts or less, 15 molar parts or less, 10 molar parts or less, 8 molar parts or less, 5 molar parts or less, 3 molar parts or less, or 2 molar parts or less, relative to 100 molar parts of Li3PS4. The larger the proportion of I2, the longer the PSS chain can be extended. The above molar ratio relationship is not limited to the case of reacting Li3PS4 with I2, but also applies to the case of reacting PS such as PS4 structure. m The present invention can also be applied to the reaction of a raw material compound containing a (m=3, 3.5, 4) unit structure (or the raw material of the raw material compound; for example, a combination of Li2S and P2S5, a combination of Na2S and P2S5, etc.) with a simple halogen.

[0044] In the step of reacting the raw material compound (C) with an oxidizing agent (reaction step), it is preferable to react the raw material compound (C) with the oxidizing agent by one or more energies selected from the group consisting of physical energy, thermal energy, and chemical energy. In the reaction step, it is preferable to react the raw material compound (C) and the oxidizing agent with energy including physical energy. The physical energy can be supplied, for example, by using a mechanochemical method (mechanical milling). For the mechanochemical method, for example, a planetary ball mill can be used. In the mechanochemical method using a planetary ball mill or the like, the treatment conditions are not particularly limited. For example, the rotation speed may be 100 rpm to 700 rpm, the treatment time may be 1 hour to 100 hours, and the ball diameter may be 1 mm to 10 mm. In the reaction step, it is preferable to react the raw material compound (C) and the oxidizing agent in a liquid. In this case, the raw material compound (C) and the oxidizing agent can be reacted in the presence of a dispersion medium. It is preferable to react the raw material compound (C) and the oxidizing agent in the presence of a dispersion medium by a mechanochemical method (mechanical milling) from the viewpoint of improving reactivity by mechanical energy. Examples of the dispersion medium include aprotic liquids, etc. The aprotic liquid is not particularly limited, and examples thereof include chain or cyclic alkanes preferably having 5 or more carbon atoms, such as n-heptane, etc., aromatic hydrocarbons, such as benzene, toluene, xylene, anisole, etc., chain or cyclic ethers, such as dimethyl ether, dibutyl ether, tetrahydrofuran, etc., alkyl halides, such as chloroform, methylene chloride, etc., and esters, such as ethyl propionate, etc.

[0045] In one embodiment, when the raw material compound (C) and the oxidizing agent are reacted in a liquid, one or both of the raw material compound (C) and the oxidizing agent can be reacted in a state mixed with a solvent. As the solvent, any of the above-mentioned dispersion media capable of dissolving either or both of the raw material compound (C) and the oxidizing agent can be used, and for example, anisole, dibutyl ether, etc. are suitable. Even in such a solution, the raw material compound (C) and the oxidizing agent can be reacted by one or more energies selected from the group consisting of physical energy such as stirring, milling, ultrasonic vibration, etc., thermal energy, and chemical energy. For example, when thermal energy is used, the solution can be heated. The heating temperature is not particularly limited and can be, for example, 40 to 200°C, 50 to 120°C, or 60 to 100°C.

[0046] In the reaction step, the compound α can be produced by oxidizing the raw material compound (C) with an oxidizing agent.

[0047] When compound α is produced by a reaction in a liquid, the liquid (dispersion medium or solvent) can be removed as necessary. By removing the liquid, a solid (powder) of compound α can be obtained. The method for removing the liquid is not particularly limited, and examples thereof include drying and solid-liquid separation, and two or more of these methods may be combined. When solid-liquid separation is used, compound α may be reprecipitated. In this case, compound α can be recovered as a solid (solid phase) by adding a liquid containing compound α to a poor solvent (poor solvent for compound α) or a non-solvent (solvent that does not dissolve compound α). For example, a method of adding n-heptane as a poor solvent to an anisole solution containing compound α and performing solid-liquid separation can be used. The solid-liquid separation means is not particularly limited, and examples thereof include evaporation, filtration, and centrifugation. When solid-liquid separation is used, an effect of improving purity can be obtained.

[0048] In one embodiment, LiI is produced as a by-product of the production of compound α. This LiI may or may not be separated from compound α. As described above, by leaving LiI as a mixture, compound α may have higher ionic conductivity. Here, the crystal phase of LiI can be, for example, c-LiI (cubic crystal) (ICSD 414244), h-LiI (hexagonal crystal) (ICSD 414242), etc. Usually, when the mechanochemical method (mechanical milling) is used as the method for producing compound α, it becomes c-LiI (cubic crystal), and when the method of reacting in a liquid (preferably in a solution) is used, it becomes h-LiI (hexagonal crystal). Whether LiI is in a certain crystal phase can be determined by powder X-ray diffraction or solid 7 Li-NMR measurement. In solid 7 Li-NMR measurement, when a peak derived from LiI (chemical shift -4.57 ppm) is observed, it is determined to be c-LiI, and when no peak derived from LiI is observed, it is determined to be h-LiI.

Examples

[0049] Examples of the present invention will be described below, but the present invention is not limited by such examples.

[0050] 1. Production of Compound α (Example 1) <Production of Li3PS4 Glass> 1.379 g of Li2S (manufactured by Furuuchi Chemical Co., 3N powder 200 Mesh) and 2.222 g of P2S5 (manufactured by Merck) were reacted under the following conditions by a mechanochemical method (mechanical milling) using a planetary ball mill (Premium Line PL-7 (Fritsch)) in the presence of a dispersion medium (n-heptane). Then, the dispersion medium was removed by drying to obtain Li3PS4 glass (powder). [Conditions of Mechanical Milling] Sample mass: 3.6 g Form: Wet milling (n-heptane: 11.7 mL) Balls: Material ZrO2, diameter 5 mm, total mass 106 g Pot: Material ZrO2, capacity 80 mL Rotation: 500 rpm Treatment time: 20 hours

[0051] <Production of Compound α> I2 (5N irregular grains (Kojundo Kagaku)) was ground in a mortar and added to the Li3PS4 glass obtained above so that the molar ratio was Li3PS4:I2=2:1. Next, the Li3PS4 glass and I2 were reacted in the presence of a dispersion medium (n-heptane) by a mechanochemical method (mechanical milling) using a planetary ball mill (Premium Line PL-7 (Fritsch)) under the following conditions. The dispersion medium was then removed by drying to obtain compound α (powder). [Mechanical milling conditions] Sample mass: 1g Format: Wet milling (n-heptane: 3mL) Ball: Material: ZrO2, diameter: 5mm, total mass: 53g Pot: Material: ZrO2, Capacity: 45mL Rotation: 500 rpm Processing time: 20 hours

[0052] Example 2 Compound α (powder) was obtained in the same manner as in Example 1, except that in the “production of compound α” of Example 1, I2 was added to Li3PS4 glass so that the molar ratio of Li3PS4:I2 was 4:3.

[0053] Example 3 Compound α (powder) was obtained in the same manner as in Example 1, except that in the “production of compound α” of Example 1, I2 was added to Li3PS4 glass so that the molar ratio of Li3PS4:I2 was 1:1.

[0054] Comparative Example 1 The "Production of compound α" in Example 1 was omitted, and the Li3PS4 glass (powder) obtained in the "Production of Li3PS4 glass" in Example 1 was evaluated.

[0055] 2. Analysis of compound α In the above examples, it was confirmed by powder X-ray diffraction (XRD), Raman spectroscopic analysis, and ionic conductivity measurement, which will be described below, that the reactions represented by the following reaction formulas (1) to (3) occurred.

[0056] Assuming that the total amount of I2 reacts with Li3PS4 by the reactions shown in the following reaction formulas (1) to (3), in the molar ratio of Example 1 (Li3PS4:I2=2:1), Li3PS4 can form one cross-link (a disulfide bond linking two phosphorus elements) on average (one S in Li3PS4 forms a cross-link). In the molar ratio of Example 2 (Li3PS4:I2=4:3), Li3PS4 can form 1.5 cross-links on average (1.5 S in Li3PS4 form a cross-link). In addition, in the molar ratio of Example 3 (Li3PS4:I2=1:1), Li3PS4 can form two cross-links on average (two S in Li3PS4 form a cross-link). The above number of cross-linking sites is merely an average value (assuming that I2 reacts evenly with Li3PS4). If I2 does not react evenly with Li3PS4, some Li3PS4 may form more cross-links and other Li3PS4 may form fewer cross-links.

[0057] [ka]

[0058] (1) Powder X-ray analysis (XRD) XRD was carried out on the compounds α (powder) obtained in Examples 1 to 3 and the Li3PS4 glass (powder) of Comparative Example 1. The results are shown in FIG. In FIG. 1, dots are added to the peaks attributable to LiI (2θ=25.2°, 29.2°, 42.1°, 49.9°, and 52.2°). 1, it was found that LiI was contained in the compound α of Examples 1 to 3. Since LiI is a product of the reaction represented by reaction formula (1) or (2), it was suggested that the reaction proceeded in Examples 1 to 3.

[0059] (2) solid31 P-NMR measurement Approximately 60 mg of compound α (powder) obtained in Examples 1 to 3 was loaded into an NMR sample tube, and solid state analysis was performed using the following apparatus and conditions. 31 P-NMR spectrum was obtained. The results for compound α obtained in Example 3 are shown in Figure 2. Equipment: ECZ400R equipment (manufactured by JEOL Ltd.) Observation kernel: 31 P Observation frequency: 161.944MHz Measurement temperature: room temperature Pulse sequence: Single pulse (uses 90° pulse) 90° Pulse width: 3.8μs Waiting time until next pulse application after FID measurement: 300 s Magic angle rotation speed: 12kHz Number of times: 16 Measurement range: 300ppm~-50ppm solid 31 In measuring the P-NMR spectrum, the chemical shifts were obtained by using (NH4)2HPO4 (chemical shift 1.33 ppm) as an external standard.

[0060] 2, a peak (signal) was clearly observed at a chemical shift of 120 ppm for compound α obtained in Example 3. This peak is considered to be derived from a PSS bond. For compound α obtained in Example 2, a similar peak was clearly observed at a chemical shift of 120 ppm. For the compound α obtained in Example 1, a peak was observed at a chemical shift of 120 ppm, although the peak was smaller than those in Examples 2 and 3.

[0061] (3) Raman spectroscopy The compound α (powder) obtained in Examples 1 to 3 and the Li3PS4 glass (powder) of Comparative Example 1 were subjected to microscopic Raman spectroscopy analysis using a laser Raman spectrophotometer ("NRS-3100" manufactured by JASCO Corporation). The results (Raman spectrum) are shown in FIG. In Comparative Example 1, the Raman shift was 420 cm-1 The peak that appears in PS4 3- This is due to the symmetric stretching of the PS bond of the unit. As the amount of I2 added increased in the order of Example 1, Example 2, and Example 3, the peak shifted to the lower wavenumber side. The reason for this is presumed to be that the PS bond was stretched by the formation of a PSS bond in the product (compound α) of the reaction shown in reaction formulas (1) to (3). In addition, in Example 12 and subsequent examples described below, a "LabRAM HR Evolution LabSpec 6" manufactured by Horiba, Ltd. was used as the laser Raman spectrophotometer.

[0062] In Examples 1 to 3, the Raman shift of 475 cm -1 A peak was confirmed near the PSS chain. The intensity of this peak increased with an increase in the amount of I2 added. From these findings, it is assumed that this peak is derived from the disulfide (SS) bond of the PSS chain. In addition, the PSSP structure was stabilized using the molecular orbital method (Gaussian09: b3lyp / 6-311++g**) and the Raman vibration calculations were performed. 3- It was found that there could be a peak due to the PS bond of the unit and a peak due to the stretching vibration of the SS bond of PSS, and it was suggested that this peak originates from the disulfide (SS) bond of the PSS chain.

[0063] <Toluene treatment> The above-mentioned Raman shift of 475 cm -1 In order to confirm that the nearby peak is not due to the disulfide (SS) bond of elemental sulfur but due to the disulfide (SS) bond of the PSS chain, the compound α sample of Example 3 was treated with toluene three times (treatment to remove elemental sulfur) and then subjected to Raman spectroscopy analysis again. The procedure for the toluene treatment is as follows. The results (Raman spectra before and after washing) are shown in Figure 4. [Toluene treatment procedure] a. 1 g of compound α is placed in a vial, and 10 mL of toluene (Fujifilm Wako Pure Chemical Industries, Ltd., ultra-dehydrated) is added, stirred, and allowed to stand. b. After removing the supernatant, add 10 mL of toluene to the solids (precipitate), stir, and allow to stand. c. Repeat step b above once. d. After removing the supernatant, the solid (precipitate) is vacuum dried at 60° C. for 10 hours to obtain toluene-treated compound α.

[0064] As shown in Figure 4, the Raman shift of 475 cm -1 It can be seen that the nearby peaks have not changed substantially (and other peaks have not changed substantially either). From this, the Raman shift of 475 cm -1 The nearby peak is presumably due to disulfide (SS) bonds in PSS chains, not disulfide (SS) bonds of elemental sulfur.

[0065] (4) Ionic conductivity Compound α (powder) obtained in Examples 1 to 3 and Li3PS4 glass (powder) of Comparative Example 1 were placed in a cylindrical container and clamped between cylindrical SUS shafts inserted from both ends of the container, and press-molded at room temperature (23°C) under a pressure of 333 MPa to be processed into a disk-shaped powder compact. While maintaining the pressed state, lead wires were connected to the powder compact and the ionic conductivity was measured using a Princeton Applied Research VersaStat 3. The ionic conductivity was calculated from the thickness of the pressed powder compact, and the results are shown in Figure 5. FIG. 5 shows that the ionic conductivity tends to decrease with an increase in the amount of I2 added (I2 / Li3PS4 ratio) (i.e., an increase in the amount of cross-linking by disulfide bonds), but it was confirmed that all samples had high ionic conductivity.

[0066] Regarding Example 3, Fig. 6 shows a scanning electron microscope (SEM) image of compound α (powder) before press molding, and Fig. 7 shows an SEM image of a fracture surface of compound α (powder compact) after press molding. As shown in Figure 6, the compound α sample (powder) before press molding has a particle size of about 1 μm to 10 μm. As shown in Figure 7, the compound α sample (powder compact) after press molding is highly densified, even though it was molded at room temperature. This shows that compound α exhibits excellent moldability.

[0067] (5)Solid 7 Li-NMR measurement Approximately 60 mg of compound α (powder) obtained in Examples 1 to 3 was loaded into an NMR sample tube, and solid state analysis was performed using the following apparatus and conditions. 7 Li-NMR measurements were performed. (Apparatus and conditions) Equipment: JNM-ECZ400R (manufactured by JEOL Ltd.) Measurement nuclei: 7 Li Measurement method: Single pulse method MAS rotation speed: 6kHz Waiting time until next 90° pulse application after FID measurement: 300 s Chemical shifts: determined using LiBr (-2.04 ppm) as an external reference

[0068] In all of the compounds α obtained in Examples 1 to 3, a peak (chemical shift -4.57 ppm) derived from LiI was observed, and therefore the crystalline phase of LiI coexisting with the compound α was determined to be c-LiI.

[0069] 3. Preparation of coating solution Example 4 Anisole was added to the compound α (powder) of Example 3 to prepare an anisole solution (coating solution) containing 33 mass% of compound α. It was confirmed that the powder of compound α was dissolved in the anisole solution. A photograph of the coating solution is shown in FIG. 8.

[0070] Example 5 A few drops of anisole were added to the compound α (powder) of Example 2 to prepare a paste-like coating liquid. It was confirmed that the coating liquid exhibited the viscosity characteristic of polymers. Figure 9 shows a photograph of the coating liquid.

[0071] Comparative Example 2 A coating solution was prepared in the same manner as in Example 4, except that the compound α (powder) of Comparative Example 1 was used instead of the compound α (powder) of Example 3. It was confirmed that the powder of compound α was not dissolved in the coating solution and precipitated. A photograph of the coating solution is shown in FIG. 10.

[0072] <Evaluation> From the results of Examples 4 and 5, it was found that by using compound α which contains phosphorus and sulfur as constituent elements and has a disulfide bond, it is possible to produce a good coating liquid having various properties such as a solution or a slurry.

[0073] 3. Manufacturing of battery sheets (1) Electrolyte layer Example 6 A slurry-like coating solution having the following composition was prepared. [Composition of coating solution] Li3PS4 solid electrolyte (Li3PS4 glass of Example 1): 95% by mass Compound α of Example 3 (powder): 5% by mass Anisole: 61 parts by mass per 100 parts by mass of the total amount (total solid content) of the Li3PS4 solid electrolyte and the compound α (powder) of Example 3

[0074] Specifically, first, 0.4 mL of anisole was added to 0.04 g of compound α (powder) of Example 3 to dissolve it. Next, 0.76 g of Li3PS4 solid electrolyte was added to the solution, and the solution was kneaded under the following kneading conditions using a planetary stirring degassing device ("MAZERUSTAR KK-250S" manufactured by Kuraray Industries, Ltd.). [Mixing conditions] Rotation: 1600 rpm Revolution: 1600 rpm Processing time: 180 seconds x 3 The sample was then treated in an ultrasonic cleaner for 5 minutes and then kneaded again under the same kneading conditions as above. Next, 0.1 mL of anisole was further added to the sample, and the mixture was further kneaded under the same kneading conditions as above to obtain a slurry-like coating liquid (slurry solid content concentration: 62% by mass).

[0075] The obtained coating solution was applied onto an aluminum foil of 5 cm × 10 cm to form a coating film, which was then dried at 60°C for 10 hours to remove the solvent (anisole) to produce a solid electrolyte sheet (sheet for batteries). The thickness of the solid electrolyte sheet (the dry coating film without aluminum foil) is about 100 μm, and the ionic conductivity is 2 × 10 -4 Scm -1 The solid electrolyte sheet did not break or peel off from the aluminum foil even when wrapped around a cylinder with a diameter of 16 mm.

[0076] A battery sheet (solid electrolyte sheet) was produced in the same manner as in Example 6, except that the compound α (powder) of Example 2 was used instead of the compound α (powder) of Example 3. When this solid electrolyte sheet was evaluated in the same manner as in Example 6, the solid electrolyte sheet did not break or peel off from the aluminum foil even when wrapped around a cylinder with a diameter of 16 mm.

[0077] Example 7 <Production of Argyrodite-type solid electrolyte> 1.284g of Li2S (Furuuchi Chemical Co., Ltd., 3N powder 200Mesh), 1.242g of P2S5 (Merck Co., Ltd.), and 0.474g of LiCl (Nacalai Tesque Co., Ltd.) were reacted in the presence of a dispersion medium (n-heptane) by mechanochemical method (mechanical milling) using a planetary ball mill (Premium Line PL-7 (Fritsch)) under the following conditions. The dispersion medium was then removed by drying to obtain a precursor of an argyrodite-type solid electrolyte. [Mechanical milling conditions] Sample mass: 3.0g Format: Wet milling (n-heptane: 11mL) Ball: Material: ZrO2, diameter: 5mm, total mass: 106g Pot: Material: ZrO2, Capacity: 80mL Rotation: 500 rpm Processing time: 20 hours 1 g of the precursor of the argyrodite-type solid electrolyte synthesized by mechanical milling was placed in a quartz tube and heat-treated at 550°C for 1 hour under an argon flow atmosphere. The heat-treated argyrodite-type solid electrolyte was pulverized in a mortar and then subjected to a micronizing treatment using a planetary ball mill (the same device as above) to obtain an argyrodite-type solid electrolyte (powder). [Conditions for fine processing] Sample mass: 0.8g Format: Wet milling (n-heptane: 13 mL, dibutyl ether: 0.25 mL) Ball: Material: ZrO2, diameter: 1mm, total mass: 40g Pot: Material: ZrO2, Capacity: 80mL Rotation: 200 rpm Processing time: 20 hours [Composition of coating solution] Argyrodite-type solid electrolyte: 95% by mass Compound α of Example 3 (powder): 5% by mass Anisole: 51 parts by mass per 100 parts by mass of the total amount (total solid content) of the argyrodite-type solid electrolyte and the compound α (powder) of Example 3 Specifically, 0.2 mL of anisole was added to dissolve 0.011 g of compound α (powder) of Example 3. Next, 0.2 g of an argyrodite-type solid electrolyte was added to the solution, and the mixture was kneaded under the following kneading conditions using a planetary stirring and defoaming device (same device as above) to obtain a slurry-like coating liquid (slurry solid content concentration 51% by mass). [Mixing conditions] Rotation: 1600 rpm Revolution: 1600 rpm Processing time: 180 seconds x 3 The obtained coating solution was applied onto an aluminum foil of 5 cm x 10 cm to form a coating film. The coating film was then dried at 60°C for 10 hours, and then vacuum dried at 160°C to remove the solvent (anisole), producing a solid electrolyte sheet (sheet for batteries). The thickness of the solid electrolyte sheet is about 45 μm, and the ionic conductivity is 4.1 × 10 -4 Scm -1 The solid electrolyte sheet did not break or peel off from the aluminum foil even when wrapped around a cylinder with a diameter of 16 mm. This indicates that compound α functions well as a binder.

[0078] Comparative Example 3 In Example 6, the compound α (powder) of Example 3 was omitted, and an attempt was made to prepare a coating solution (solid content concentration 62% by mass) in which the total amount of solid content was Li3PS4 solid electrolyte. However, at a solid content concentration of 62% by mass, the solid content remained solid, and no coating solution was obtained. When the solid content concentration was then diluted with anisole to 53% by mass, a slurry-like coating solution was obtained. A solid electrolyte sheet (battery sheet) was produced in the same manner as in Example 6 using this coating solution (solid content concentration 53% by mass). When the obtained solid electrolyte sheet was wound around a cylinder with a diameter of 16 mm, the sheet broke and peeled off from the aluminum foil.

[0079] (2) Positive electrode (battery electrode mixture layer) Example 8 <LiNbO3 coating on positive electrode active material> LiNi 1 / 3 Mn 1 / 3 Co 1 / 3200 mg of O2(NMC) (MTI) was weighed out, and 0.3 mL of LiNb(OEt)6 (Alfa Aesar, lithium niobium ethoxide, 99+% (metal base), 5% w / v in ethanol) was added to it. Next, 0.7 mL of ultra-dehydrated ethanol (Fujifilm Wako Pure Chemical Industries, Ltd.) was added to it. The obtained sample was treated in an ultrasonic cleaner for 30 minutes and dried at 40°C for 10 hours in an Ar atmosphere. The sample was then vacuum dried at 100°C for 1 hour. The dried sample was placed in a desiccator with a relative humidity of about 40% to 50%, and the hydrolysis reaction was allowed to proceed for 10 hours. Next, the sample after the reaction was heat-treated at 350°C for 1 hour to obtain LiNi coated with LiNbO3. 1 / 3 Mn 1 / 3 Co 1 / 3 O2 (LiNbO3-coated NMC) was obtained. The LiNbO3 content in the obtained LiNbO3-coated NMC was 3 mass%. <Preparation of positive electrode sheet> LiNbO3 coated LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2 (LiNbO3-coated NMC), the same argyrodite-type solid electrolyte (SE) as in Example 7, and acetylene black (AB) (manufactured by Denka Co., Ltd.) were mixed in a mass ratio of LiNbO3-coated NMC:SE:AB=70:30:5 (total mass 0.24 g). 0.1 mL of anisole solution containing compound α (powder) of Example 3 at a concentration of 10 mass% was added to the obtained mixture. The composition after the addition was LiNbO3-coated NMC:SE:compound α:AB=70:30:5:5. This composition was kneaded, and about 0.1 mL to 0.2 mL of anisole was further added and kneaded again to obtain a slurry (solid concentration 40 to 60 mass%). The obtained slurry was applied onto an Al foil of 5 × 10 cm to form a coating film. The coating film was 60 o After drying at C for 10 hours, o The sheet was then vacuum dried at C for 3 hours. The resulting sheet was punched out with a punch to obtain a positive electrode sheet having a diameter of 9.5 mm. The positive electrode sheet did not break or peel off from the aluminum foil even when wrapped around a cylinder with a diameter of 16 mm. The positive electrode sheet also could be easily punched out. This indicates that compound α functions well as a binder.

[0080] Example 9 <Production of all-solid-state batteries> Li3PS4 solid electrolyte (Li3PS4 glass of Example 1) (80 mg) was placed in a cylindrical container with SUS shafts on both sides and pressed to form a solid electrolyte layer. Next, the positive electrode sheet obtained in Example 8 was placed in the cylindrical container so as to overlap with the solid electrolyte layer, and further, In foil and Li foil were placed in this order on the side of the solid electrolyte layer in the cylindrical container opposite the electrode sheet, and press-laminated to prepare a test cell. The cell was restrained with a dedicated jig and tested for the following battery characteristics.

[0081] <Initial characteristics> The results of the initial charge and discharge are shown in FIG. From FIG. 11, it was found that the cell including the positive electrode sheet of Example 8 was capable of charging and discharging without any significant side reactions.

[0082] <Cycle characteristics> The results of the cycle characteristics are shown in FIG. 12, it was found that the cell including the positive electrode sheet of Example 8 had good cycle characteristics, which demonstrated that the compound α functioned well as a binder for the positive electrode sheet.

[0083] <AC impedance measurement> For the cell including the positive electrode sheet of Example 8, AC impedance measurement was performed using a Solartron 1470E Cell test system manufactured by Solartron Analytical, and a Cole-Cole plot was obtained. The result (Cole-Cole plot) is shown in FIG. From FIG. 13, it was found that the cell including the positive electrode sheet of Example 8 had a small interface resistance after charging, and therefore the compound α functioned well as a binder.

[0084] (3) Negative electrode (battery electrode mixture layer) Example 10 <Preparation of negative electrode sheet> Graphite (manufactured by Nippon Graphite Co., Ltd.), the argyrodite-type solid electrolyte (SE) of Example 7, and acetylene black (AB) were mixed in a mass ratio of graphite:SE:AB=60:40:1 (total mass 0.23 g). 0.1 mL of anisole solution containing compound α (powder) of Example 3 at a concentration of 10 mass% was added to the obtained mixture. The composition after the addition was graphite:SE:compound α:AB=60:40:5:1. This composition was kneaded, and about 0.1 mL to 0.2 mL of anisole was further added and kneaded again to obtain a slurry (solid concentration 40 to 60 mass%). The obtained slurry was applied onto a Cu foil of 5×10 cm to form a coating film. The coating film was dried at 60°C for 10 hours, and then vacuum dried at 160°C for 3 hours. The obtained sheet was punched out with a punch to obtain a negative electrode sheet with a diameter of 9.5 mm. The negative electrode sheet did not break or peel off from the Cu foil even when wrapped around a cylinder with a diameter of 16 mm. The negative electrode sheet also could be easily punched out. This indicates that compound α functions well as a binder.

[0085] Example 11 <Production of all-solid-state batteries> Li3PS4 solid electrolyte (Li3PS4 glass of Example 1) (80 mg) was placed in a cylindrical container with SUS shafts on both sides and pressed to form a solid electrolyte layer. Next, the negative electrode sheet obtained in Example 10 was placed in the cylindrical container so as to overlap with the solid electrolyte layer, and further, In foil and Li foil were placed in this order on the side opposite the electrode sheet in the solid electrolyte layer in the cylindrical container, and press-laminated to prepare a test cell. The cell was restrained with a dedicated jig and tested for the following battery characteristics.

[0086] <Initial characteristics> The results of the initial charge and discharge are shown in FIG. From FIG. 14, it was found that the cell including the negative electrode sheet of Example 9 had a large irreversible capacity in the initial cycles, but gradually became stable from the second cycle onwards.

[0087] <Cycle characteristics> The results of the cycle characteristics are shown in FIG. 15, it can be seen that the cell including the negative electrode sheet of Example 9 has good cycle characteristics, which indicates that the compound α functions well as a binder for the negative electrode sheet.

[0088] Example 12 Compound α (powder) was obtained in the same manner as in Example 1, except that in the “production of compound α” of Example 1, I2 was added to Li3PS4 glass so that the molar ratio was Li3PS4:I2=4:5. The obtained compound α (powder) was subjected to Raman spectroscopic analysis in the same manner as in Example 1. The Raman shift was 475 cm -1 Nearby (477cm -1 In the description of Example 12 and onwards, a peak at a Raman shift of 475 cm -1 When a peak was confirmed nearby, a peak corresponding to peak B was also confirmed separately.

[0089] Example 13 In the "Production of Compound α" of Example 1, the molar ratio of Li3PS4 glass to I2 was Li3PS4:I2=1:1, and instead of the mechanochemical method, Li3PS4 glass and I2 were dissolved in a solvent (anisole) to prepare a solution, and the solution was reacted at 60°C for 24 hours while stirring. Next, the solvent was removed by drying to obtain Compound α (powder). The obtained compound α (powder) was subjected to Raman spectroscopic analysis in the same manner as in Example 1. The Raman shift was 475 cm -1 Nearby (477cm -1 ) peak was confirmed. When the obtained compound α (powder) was subjected to XRD in the same manner as in Example 1, a peak due to LiI was observed, suggesting that the reaction represented by reaction formula (1) or (2) had proceeded. The obtained compound α (powder) was subjected to solidification in the same manner as in Example 1. 31 A P-NMR spectrum was obtained, and a peak was observed at a chemical shift of 120 ppm, as shown in FIG. The obtained compound α (powder) was subjected to solidification in the same manner as in Example 1. 7 When Li-NMR was measured, no peaks derived from LiI were observed, and therefore it was determined that the crystalline phase of LiI coexisting with compound α was h-LiI. A battery sheet (solid electrolyte sheet) was produced from the obtained compound α (powder) in the same manner as in Example 6 and evaluated. The solid electrolyte sheet was neither broken nor peeled off from the aluminum foil even when wrapped around a cylinder with a diameter of 16 mm. In addition, n-heptane was added to the solution after the synthesis reaction of compound α to separate the solid and liquid, and the solid portion was collected. The solid portion was dried to obtain a powder sample. When the powder sample was subjected to Raman spectroscopy in the same manner as in Example 1, a Raman shift of 475 cm -1 Nearby (479cm -1 ) peak (derived from the disulfide (SS) bond of the PSS chain) was confirmed.

[0090] Example 14 Compound α (powder) was obtained in the same manner as in Example 13, except that the reaction time was changed to 72 hours. The obtained compound α (powder) was subjected to Raman spectroscopic analysis in the same manner as in Example 1. The Raman shift was 475 cm -1 Nearby (477cm -1 ) peak was confirmed. A battery sheet (solid electrolyte sheet) was produced from the obtained compound α (powder) in the same manner as in Example 6 and evaluated. The solid electrolyte sheet was neither broken nor peeled off from the aluminum foil even when wrapped around a cylinder with a diameter of 16 mm. The ionic conductivity was 4.2×10 -4 Scm -1 It was. In the production of the solid electrolyte sheet, when the concentration of the compound α in the coating solution is 10 mass %, the ionic conductivity of the solid electrolyte sheet is 2.6 × 10-4 Scm -1 In addition, when the concentration of compound α in the coating solution was 15 mass %, the ionic conductivity of the solid electrolyte sheet was 2.4 × 10 -4 Scm -1 It was.

[0091] Example 15 Compound α (powder) was obtained in the same manner as in Example 13, except that the reaction time was changed to 96 hours. The obtained compound α (powder) was subjected to Raman spectroscopic analysis in the same manner as in Example 1. The Raman shift was 475 cm -1 Nearby (477cm -1 ) peak was confirmed. The obtained compound α (powder) was subjected to solidification in the same manner as in Example 1. 31 A P-NMR spectrum was obtained, and a peak was observed at a chemical shift of 120 ppm. In addition, a battery sheet (solid electrolyte sheet) was produced from the obtained compound α (powder) in the same manner as in Example 6 and evaluated. The solid electrolyte sheet was neither broken nor peeled off from the aluminum foil even when wrapped around a cylinder with a diameter of 16 mm. The ionic conductivity was 1.7×10 -4 Scm -1 It was. Furthermore, the suitability of the obtained compound α (powder) for a positive electrode sheet was evaluated. Specifically, in Example 7, the compound α (powder) obtained in Example 15 was used instead of the compound α (powder) in Example 3 to obtain an argyrodite-type solid electrolyte (SE). Next, in Example 8, the compound α (powder) obtained in Example 15 was used instead of the compound α (powder) in Example 3, and the Li3PS4 solid electrolyte (SE) obtained as above was used to obtain a positive electrode sheet. The obtained positive electrode sheet did not break or peel off from the Al foil even when wrapped around a cylinder with a diameter of 16 mm. In addition, the positive electrode sheet could be punched out well with a punch. This shows that the compound α functions well as a binder.

[0092] Example 16 Compound α (powder) was obtained in the same manner as in Example 13, except that the reaction time was changed to 216 hours. The obtained compound α (powder) was subjected to Raman spectroscopic analysis in the same manner as in Example 1. The Raman shift was 475 cm -1 Nearby (477cm -1 ) peak was confirmed. In addition, the obtained compound α (powder) was subjected to solidification in the same manner as in Example 1. 31 A P-NMR spectrum was obtained, and a peak was observed at a chemical shift of 120 ppm.

[0093] (Example 17) Compound α (powder) was obtained in the same manner as in Example 13, except that the reaction temperature was 80°C. The obtained compound α (powder) was subjected to Raman spectroscopic analysis in the same manner as in Example 1. The Raman shift was 475 cm -1 Nearby (477cm -1 ) peak was confirmed. A battery sheet (solid electrolyte sheet) was produced from the obtained compound α (powder) in the same manner as in Example 6 and evaluated. The solid electrolyte sheet was neither broken nor peeled off from the aluminum foil even when wrapped around a cylinder with a diameter of 16 mm.

[0094] (Example 18) Compound α (powder) was obtained in the same manner as in Example 13, except that the reaction temperature was 100° C. and the reaction time was 1 hour. The obtained compound α (powder) was subjected to Raman spectroscopic analysis in the same manner as in Example 1. The Raman shift was 475 cm -1 Nearby (477cm -1 ) peak was confirmed. When the obtained compound α (powder) was subjected to XRD in the same manner as in Example 1, a peak due to LiI was observed, suggesting that the reaction represented by reaction formula (1) or (2) had proceeded. A battery sheet (solid electrolyte sheet) was produced from the obtained compound α (powder) in the same manner as in Example 6 and evaluated. The solid electrolyte sheet was neither broken nor peeled off from the aluminum foil even when wrapped around a cylinder with a diameter of 16 mm.

[0095] (Example 19) Compound α (powder) was obtained in the same manner as in Example 13, except that the molar ratio of Li3PS4 glass to I2 was Li3PS4:I2=4:5. The obtained compound α (powder) was subjected to Raman spectroscopic analysis in the same manner as in Example 1. The Raman shift was 475 cm -1 Nearby (477cm -1 ) peak was confirmed. When the obtained compound α (powder) was subjected to XRD in the same manner as in Example 1, a peak due to LiI was observed, suggesting that the reaction represented by reaction formula (1) or (2) had proceeded. The obtained compound α (powder) was subjected to solidification in the same manner as in Example 1. 7 When Li-NMR was measured, no peaks derived from LiI were observed, and therefore it was determined that the crystalline phase of LiI coexisting with compound α was h-LiI. A battery sheet (solid electrolyte sheet) was produced from the obtained compound α (powder) in the same manner as in Example 6 and evaluated. The solid electrolyte sheet was neither broken nor peeled off from the aluminum foil even when wrapped around a cylinder with a diameter of 16 mm. The ionic conductivity was 3.9×10 -4 Scm -1 It was.

[0096] (Example 20) Compound α (powder) was obtained in the same manner as in Example 19, except that the reaction temperature was 80° C. and the reaction time was 96 hours. The obtained compound α (powder) was subjected to Raman spectroscopic analysis in the same manner as in Example 1. The Raman shift was 475 cm -1 Nearby (477cm -1 ) peak was confirmed. In addition, a battery sheet (solid electrolyte sheet) was produced from the obtained compound α (powder) in the same manner as in Example 6 and evaluated. The solid electrolyte sheet was neither broken nor peeled off from the aluminum foil even when wrapped around a cylinder with a diameter of 16 mm.

[0097] Example 21 Compound α (powder) was obtained in the same manner as in Example 19, except that the reaction temperature was 100° C. and the reaction time was 24 hours. The obtained compound α (powder) was subjected to Raman spectroscopic analysis in the same manner as in Example 1. The Raman shift was 475 cm -1 Nearby (477cm -1 ) peak was confirmed.

[0098] Example 22 Compound α (powder) was obtained in the same manner as in Example 13, except that the molar ratio of Li3PS4 glass to I2 was Li3PS4:I2=2:1 and the reaction temperature was 60°C. The obtained compound α (powder) was subjected to Raman spectroscopic analysis in the same manner as in Example 1. The Raman shift was 475 cm -1 Nearby (477cm -1 ) peak was confirmed. When the obtained compound α (powder) was subjected to XRD in the same manner as in Example 1, a peak due to LiI was observed, suggesting that the reaction represented by reaction formula (1) or (2) had proceeded. The obtained compound α (powder) was subjected to solidification in the same manner as in Example 1. 7 When Li-NMR was measured, no peaks derived from LiI were observed, and therefore it was determined that the crystalline phase of LiI coexisting with compound α was h-LiI.

[0099] Example 23 Compound α (powder) was obtained in the same manner as in Example 22, except that the molar ratio of Li3PS4 glass to I2 was Li3PS4:I2=4:3. The obtained compound α (powder) was subjected to Raman spectroscopic analysis in the same manner as in Example 1. The Raman shift was 475 cm -1 Nearby (477cm -1 ) peak was confirmed. When the obtained compound α (powder) was subjected to XRD in the same manner as in Example 1, a peak due to LiI was observed, suggesting that the reaction represented by reaction formula (1) or (2) had proceeded. The obtained compound α (powder) was subjected to solidification in the same manner as in Example 1. 7 When Li-NMR was measured, no peaks derived from LiI were observed, and therefore it was determined that the crystalline phase of LiI coexisting with compound α was h-LiI.

[0100] (Example 24) Compound α (powder) was obtained in the same manner as in Example 22, except that the molar ratio of Li3PS4 glass to I2 was Li3PS4:I2=1:1 and the reaction temperature was room temperature (23° C.). The obtained compound α (powder) was subjected to Raman spectroscopic analysis in the same manner as in Example 1. The Raman shift was 475 cm -1 Nearby (477cm -1 ) peak was confirmed.

[0101] (Example 25) Compound α (powder) was obtained in the same manner as in Example 13, except that Br2 was used instead of I2 and the molar ratio of Li3PS4 glass to Br2 was Li3PS4:Br2=1:1. The obtained compound α (powder) was subjected to Raman spectroscopic analysis in the same manner as in Example 1. The Raman shift was 475 cm -1 Nearby (477cm -1 ) peak was confirmed. When the obtained compound α (powder) was subjected to XRD in the same manner as in Example 1, a peak due to LiBr was observed, suggesting that the reaction represented by reaction formula (1) or (2) (wherein I is replaced by Br) had proceeded.

[0102] (Example 26) Compound α (powder) was obtained in the same manner as in Example 25, except that dibutyl ether was used instead of anisole as the solvent. The obtained compound α (powder) was subjected to Raman spectroscopic analysis in the same manner as in Example 1. The Raman shift was 475 cm -1 Nearby (477cm -1 ) peak was confirmed. When the obtained compound α (powder) was subjected to XRD in the same manner as in Example 1, a peak due to LiBr was observed, suggesting that the reaction represented by reaction formula (1) or (2) (wherein I is replaced by Br) had proceeded.

[0103] Example 27 Li4P2S7 glass was obtained in the same manner as in Example 1 for producing Li3PS4 glass, except that the amounts of Li2S and P2S5 charged were set to a predetermined ratio (molar ratio of Li2S:P2S5=2:1). Compound α (powder) was obtained in the same manner as in Example 1, except that Li4P2S7 glass was used instead of Li3PS4 glass and the molar ratio of Li4P2S7 glass to I2 was Li4P2S7:I2=2:1. The obtained compound α (powder) was subjected to Raman spectroscopic analysis in the same manner as in Example 1. The Raman shift was 475 cm -1 Nearby (480cm -1 ) peak was confirmed.

[0104] (Example 28) Compound α (powder) was obtained in the same manner as in Example 27, except that the molar ratio of Li4P2S7 glass to I2 was Li4P2S7:I2=4:3. The obtained compound α (powder) was subjected to Raman spectroscopic analysis in the same manner as in Example 1. The Raman shift was 475 cm -1 Nearby (480cm -1 ) peak was confirmed.

[0105] (Example 29) Compound α (powder) was obtained in the same manner as in Example 27, except that the molar ratio of Li4P2S7 glass to I2 was Li4P2S7:I2=8:7. The obtained compound α (powder) was subjected to Raman spectroscopic analysis in the same manner as in Example 1. The Raman shift was 475 cm -1 Nearby (480cm -1 ) peak was confirmed. In addition, when the obtained compound α (powder) was subjected to XRD in the same manner as in Example 1, a peak due to LiI was observed, suggesting that the reaction represented by reaction formula (1) or (2) had proceeded.

[0106] (Example 30) Compound α (powder) was obtained in the same manner as in Example 27, except that the molar ratio of Li4P2S7 glass to I2 was Li4P2S7:I2=1:1. The obtained compound α (powder) was subjected to Raman spectroscopic analysis in the same manner as in Example 1. The Raman shift was 475 cm -1 Nearby (480cm -1 ) peak was confirmed. When the obtained compound α (powder) was subjected to XRD in the same manner as in Example 1, a peak due to LiI was observed, suggesting that the reaction represented by reaction formula (1) or (2) had proceeded. In addition, a battery sheet (solid electrolyte sheet) was produced from the obtained compound α (powder) in the same manner as in Example 6 and evaluated. The solid electrolyte sheet was neither broken nor peeled off from the aluminum foil even when wrapped around a cylinder with a diameter of 16 mm. The ionic conductivity was 2.8×10 -4 Scm -1 It was.

[0107] (Example 31) Compound α (powder) was obtained in the same manner as in Example 1, except that in Example 27, the molar ratio of Li4P2S7 glass to I2 was Li4P2S7:I2=2:3. The obtained compound α (powder) was subjected to Raman spectroscopic analysis in the same manner as in Example 1. The Raman shift was 475 cm -1Nearby (480cm -1 ) peak was confirmed. In addition, when the obtained compound α (powder) was subjected to XRD in the same manner as in Example 1, a peak due to LiI was observed, suggesting that the reaction represented by reaction formula (1) or (2) had proceeded.

[0108] Example 32 Compound α (powder) was obtained in the same manner as in Example 13, except that Li4P2S7 glass was used instead of Li3PS4 glass, the molar ratio of Li4P2S7 glass to I2 was Li4P2S7:I2=1:1, and the reaction time was 6 hours. The obtained compound α (powder) was subjected to Raman spectroscopic analysis in the same manner as in Example 1. The Raman shift was 475 cm -1 Nearby (477cm -1 ) peak was confirmed.

[0109] (Example 33) Compound α (powder) was obtained in the same manner as in Example 13, except that Li2S and P2S5 were used instead of Li3PS4 and the molar ratio of Li2S, P2S5 and I2 was Li2S:P2S5:I2=3:1:2. The obtained compound α (powder) was subjected to Raman spectroscopic analysis in the same manner as in Example 1. The Raman shift was 475 cm -1 Nearby (477cm -1 ) peak was confirmed.

[0110] (Example 34) Compound α (powder) was obtained in the same manner as in Example 33, except that the reaction temperature was 100°C. The obtained compound α (powder) was subjected to Raman spectroscopic analysis in the same manner as in Example 1. The Raman shift was 475 cm -1 Nearby (477cm -1 ) peak was confirmed. In addition, when the obtained compound α (powder) was subjected to XRD in the same manner as in Example 1, a peak due to LiI was observed, suggesting that the reaction represented by reaction formula (1) or (2) had proceeded.

[0111] Example 35 Compound α (powder) was obtained in the same manner as in Example 33, except that dibutyl ether was used instead of anisole as the solvent. The obtained compound α (powder) was subjected to Raman spectroscopic analysis in the same manner as in Example 1. The Raman shift was 475 cm -1 Nearby (477cm -1 ) peak was confirmed.

[0112] (Example 36) Compound α (powder) was obtained in the same manner as in Example 1, except that Na3PS4 was used instead of Li3PS4 and the molar ratio of Na3PS4 to I2 was Na3PS4:I2=2:1. The obtained compound α (powder) was subjected to Raman spectroscopic analysis in the same manner as in Example 1. The Raman shift was 475 cm -1 Nearby (474cm -1 ) peak was confirmed. When the obtained compound α (powder) was subjected to XRD in the same manner as in Example 1, a peak due to NaI was observed, suggesting that the reaction represented by reaction formula (1) or (2) (where Li is replaced by Na) had proceeded.

[0113] (Example 37) Compound α (powder) was obtained in the same manner as in Example 36, except that the molar ratio of Na3PS4 to I2 was Na3PS4:I2=4:3. The obtained compound α (powder) was subjected to Raman spectroscopic analysis in the same manner as in Example 1. The Raman shift was 475 cm -1 Nearby (474cm -1 ) peak was confirmed. When the obtained compound α (powder) was subjected to XRD in the same manner as in Example 1, a peak due to NaI was observed, suggesting that the reaction represented by reaction formula (1) or (2) (where Li is replaced by Na) had proceeded.

[0114] (Example 38) Compound α (powder) was obtained in the same manner as in Example 36, except that the molar ratio of Na3PS4 to I2 was Na3PS4:I2=1:1. The obtained compound α (powder) was subjected to Raman spectroscopic analysis in the same manner as in Example 1. The Raman shift was 475 cm -1 Nearby (474cm -1 ) peak was confirmed. When the obtained compound α (powder) was subjected to XRD in the same manner as in Example 1, a peak due to NaI was observed, suggesting that the reaction represented by reaction formula (1) or (2) (where Li is replaced by Na) had proceeded.

[0115] (Example 39) Compound α (powder) was obtained in the same manner as in Example 36, except that the molar ratio of Na3PS4 to I2 was Na3PS4:I2=4:5. The obtained compound α (powder) was subjected to Raman spectroscopic analysis in the same manner as in Example 1. The Raman shift was 475 cm -1 Nearby (474cm -1 ) peak was confirmed. When the obtained compound α (powder) was subjected to XRD in the same manner as in Example 1, a peak due to NaI was observed, suggesting that the reaction represented by reaction formula (1) or (2) (where Li is replaced by Na) had proceeded.

[0116] Comparative Example 4 A battery sheet (solid electrolyte sheet) was produced and evaluated in the same manner as in Example 6, except that styrene-butadiene thermoplastic elastomer (SBS) was used instead of compound α (powder). The solid electrolyte sheet did not break or peel off from the aluminum foil even when wrapped around a cylinder with a diameter of 16 mm. However, the ionic conductivity was 1.1×10 -4 Scm -1 It was inferior to that.

[0117] Although the present invention has been described above with reference to some embodiments and examples, the present invention is not limited to these, and various modifications are possible within the scope of the gist of the present invention. The present invention includes configurations that are substantially the same as those described in the embodiments (for example, configurations with the same functions, methods, and results, or configurations with the same purpose and effect). The present invention also includes configurations in which non-essential parts of the configurations described in the above embodiments are replaced with other configurations. Furthermore, the present invention also includes configurations that have the same effects as the configurations described in the above embodiments, or that can achieve the same purpose. Furthermore, the present invention also includes configurations in which publicly known technology is added to the configurations described in the above embodiments.

[0118] Although some embodiments and / or examples of the present invention have been described in detail above, those skilled in the art can easily make many modifications to these exemplary embodiments and / or examples without substantially departing from the novel teachings and advantages of the present invention, and therefore many such modifications are within the scope of the present invention. The contents of all documents cited in this specification and of the application from which this application claims priority under the Paris Convention are incorporated by reference in their entirety.

Claims

1. A compound containing lithium, phosphorus and sulfur as constituent elements, and having, in Raman spectroscopic analysis, a peak derived from a disulfide bond linking two phosphorus elements and a peak derived from a PS 4 bond.

2. A binder for a battery comprising the compound of claim 1.

3. 3. The battery binder of claim 2, comprising a halogen.

4. 4. The battery binder of claim 3, wherein the halogen is iodine or bromine.

5. A battery electrode mixture layer or electrolyte layer comprising the battery binder according to any one of claims 2 to 4.

6. The battery electrode mixture layer or electrolyte layer according to claim 5 , further comprising a solid electrolyte other than the battery binder.

7. A sheet for a battery comprising at least one selected from the group consisting of the electrode mixture layer for a battery according to claim 5 or 6 and an electrolyte layer.

8. A battery comprising the compound of claim 1.

9. Constituent elements include lithium, phosphorus and sulfur, and PS 4 adding an oxidizing agent to a raw compound containing the structure; reacting said raw material compound with said oxidizing agent; Including, A method for producing a compound, wherein the produced compound has a peak derived from a PS 4 bond in Raman spectroscopy.

10. A method for producing a compound containing lithium, phosphorus and sulfur as constituent elements, and having a peak derived from a disulfide bond linking two phosphorus elements and a peak derived from a PS4 bond in Raman spectroscopic analysis, comprising the steps of: Adding an oxidizing agent to a raw material compound containing lithium, phosphorus and sulfur as constituent elements; and reacting said raw material compound with said oxidizing agent; A method for producing a compound, comprising:

11. The method for producing a compound according to claim 9 or 10, wherein the oxidizing agent is a halogen alone.

12. The method for producing a compound according to claim 11, wherein the halogen element is iodine or bromine.

13. The method for producing a compound according to any one of claims 9 to 12, wherein the raw material compound and the oxidizing agent are reacted with one or more energy sources selected from the group consisting of physical energy, thermal energy, and chemical energy.

14. The method for producing the compound according to any one of claims 9 to 13, wherein the raw material compound and the oxidizing agent are reacted in a liquid.

Citation Information

Patent Citations

  • Process for the preparation of highly purified, dialkydithiophosphinic compounds

    US20080103330A1